Efficient production of biodiesel at low temperature using highly active bifunctional Na-Fe-Ca nanocatalyst from blast furnace waste. (15th August 2022) - Wang, Yi-Tong; Wang, Xiao-Man; Gao, Di; Wang, Fu-Ping; Zeng, Ya-Nan; Li, Jun-Guo; Jiang, Li-Qun; Yu, Qing; Ji, Rui; Kang, Le-Le; Wang, Ya-Jun; Fang, Zhen
Graphical abstract: Highlights: Blast furnace dust (BFD) was impregnated and calcined as heterogeneous catalysts. Biodiesel yield of 100 wt% (Na-BFD) and 98.3 wt% (Ca-BFD) was achieved at 65 °C. Na-BFD500 achieved 95.8 wt% yield for 16 cycles by nano-components NaFeO2 & Ca2 Fe2 O5 . Ca-BFD600 reached 94.1 wt% yield for 7 cycles by nano-components CaO & Ca2 Fe2 O5 . Fe2 O3 and CaCO3 in BFD were converted to magnetic and active components. Abstract: In this study, nanocatalysts for biodiesel production were prepared via wet impregnation of blast furnace dust (BFD) in Na2 CO3 (Na-BFD) and CaCO3 (Ca-BFD) suspension solutions and calcination at 500 and 600 °C, respectively. Biodiesel yields of 100.0 wt% (Na-BFD500 ) and 98.3 wt% (Ca-BFD600 ) were achieved at 65 °C. Synthesized catalysts showed outstanding activity and recyclability, due to the transition of CaCO3, Na2 CO3 and Fe2 O3 to nanocrystals of NaFeO2 (29.9 nm), Ca2 Fe2 O5 (10.5 nm), CaO (100.1 nm) and Ca2 Fe2 O5 (50.0 nm). Na-BFD500 achieved 95.8 wt% biodiesel yield with 16 cycles, whereas Ca-BFD600 reached 94.1 wt% biodiesel yield with 7 cycles via magnetic separation. BFD containing convertible magnetic and active components (Fe2 O3 and CaCO3 ) was an ideal raw material to synthesize catalyst for biodiesel production with high catalytic efficiency and easy separation. The study provided a practical utilization of industrial solid waste for biodiesel production.